PARASITE WORM. (World Bulletin of Public Health, 2024)
Parasite worms are a significant concern in global health, particularly in tropical and subtropical regions. This article examines the various types of parasitic worms, their effects on human health, and the methods used to control them. The analysis is based on current scientific literature, highlighting both the biological characteristics of these parasites and the social implications of infections. Various diagnostic, preventive, and treatment methods are discussed, concluding with recommendations for future research and public health strategies
Keywords: Parasite worms; helminths; infections